A comparison of CPAP and CPAPFLEX in the treatment of obstructive sleep apnea in World Trade Center responders: study protocol for a randomized controlled trial. Issue 1 (December 2015) - Ayappa, Indu; Sunderram, Jag; Black, Kathleen; Twumasi, Akosua; Udasin, Iris; Harrison, Denise; Carson, Jeffrey; Lu, Shou-En; Rapoport, David
Abstract Background Following the World Trade Center disaster, a large number of individuals involved in rescue and recovery activity were exposed to significant amounts of dust, and reported symptoms of chronic nasal and sinus inflammation. An unusually high prevalence of obstructive sleep apnea (OSA) has also been observed in this World Trade Center Responder population. This project aims to examine the relationship between nasal pathology and OSA. Our hypothesis is that increased nasal resistance due to nasal inflammation predisposes to OSA in this population. Continuous Positive Airway Pressure (CPAP) is the standard therapy for OSA but despite its efficacy has poor adherence. Subjects with high nasal resistance may have greater difficulty in tolerating this therapy than those who do not have high nasal resistance. Reduction of excess expiratory positive pressure by the modality known as Cflex™ during Continuous Positive Airway Pressure therapy (CPAPFlex ) has been suggested to improve comfort without compromising efficacy. We will compare CPAP to CPAPFlex in subjects with OSA. Study Design Subjects with new onset habitual snoring will be screened for OSA using home sleep studies and rhinomanometry will be used to determine nasal resistance. In 400 subjects with OSA we will perform a randomized double blind cross-over study comparing CPAP to CPAPflex, and relate nasal resistance to adherence to CPAP therapy. Discussion This is the first multicenter trial designed to test the hypothesis that adherence to CPAP therapy relates to nasal resistance and CPAPFlex will improve adherence to CPAP in those subjects with high nasal resistance. We anticipate the following results from this trial: 1. Increased nasal resistance is associated with decreased adherence to CPAP therapy. 2. Use of CPAPFlex improves adherence with CPAP therapy in subjects with high nasal resistance, but not in those with low nasal resistance. 3. The benefit of CPAPFlex on adherence is greatest when offered at CPAP therapy initiation rather than as a "rescue" therapy in subjects with high nasal resistance. Trial Registration ClinicalTrials.gov Identifier:NCT01753999, Date: 12 December 2012